DEBT, PAYBACK, AND THE SUSTAINABILITY THROUGH THE VEGETAL IMAGINATION: ATWOOD’S PAYBACK AND HAN KANG’S THE VEGETARIAN - Lee, Jihyun (PEOPLE: International Journal of Social Sciences, 2017)
This paper is a close reading of Han Kang’s ‘The Vegetarian’ centrally in relation to the author’s notion of ‘innocence’ and to Margaret Atwood’s notion of ‘debt’ and ‘payback’. Building upon this foundation, Gaston Bachelard’s concept of the ‘vegetal imagination’ will then be incorporated into the paper’s broader psychoanalytic context as a means of explaining the protagonist, Yeong- hye’s relationship to moral debt. What is important to understand for this paper is that the vegetal imagination embraces contradiction. In this respect, the vegetal imagination can be seen as sympathetic towards both human beings and nature, aiming for sustainability. Actually, Han portrays Yeong-hye as the epitome of someone trying to embrace the victims of a violent history, symbolized in the novel as uprooted trees.